Modelo de negocio para la creación de una empresa de servicios de mantenimiento domiciliario en el cantón Latacunga. - Chanatasig Guanoluisa, Luis Eduardo (2021)
Business models have become an almost essential innovation tool for the creation and success of companies, since it allows to clearly know the type of business that is going to be created and introduced in the market and how a company creates, offers and captures value from a market segment. The business model proposed for the creation of a home maintenance services company in Latacunga canton, seeks to propose a solution to the problem of contacting and contracting house maintenance such as electricity, plumbing, masonry, in a comprehensive, fast, safe way and confiable. The methodological approach considered for the development of the research is quantitative, which is supported by the deductive method, in order to obtain conclusions from the general to the particular. To collect information about needs, preferences, supply, unsatisfied demand and other information that significantly contributes to the development of the business model, electronic surveys applied to owners of 382 homes in Latacunga canton were used, determined by applying the simple random probability sampling research technique. For the development of the business model, the CANVAS model proposed by Osterwalder and Pigneur (2011) is considered, because they propose a general concept where the strategy is part of the business model, which responds to a holistic definition; the proposed business model can be used as a guide for the development of future projects aimed at the real estate service field.